A decade comparison of regulatory decision patterns for oncology products to all other non‐oncology products among Swissmedic, European Medicines Agency, and US Food and Drug Administration - Ulrich‐P. Rohr; Mario Iovino; Leonie Rudofsky; Qiyu Li; Stephanie Juritz; Arunas Gircys; Oliver Wildner; Magda Bujar; Claus Bolte; Simon Dalla Torre di Sanguinetto; Anita Wolfer (Wiley, 2023)
Abstract Consensus of regulatory decisions on the same Marketing Authorization Application (MAA) are critical for stakeholders. In this context, regulatory decision patterns from the Swissmedic (SMC), the US Food and Drug Administration (FDA), and the European Medicines Agency (EMA) were analyzed for hemato‐oncology products (OP) and non‐oncology products (NOP). We compared 336 SMC regulatory decisions between 2009 and 2018 on new active substances with the EMA and the FDA for OP (n = 77) and NOP (n = 259) regarding approval rates, consensus, and divergent decisions. For OP MAA, we analyzed the underlying reasons for divergent decisions; for consensus decisions, the similarity and strictness of labeling. For OP, the approval rate for the SMC was 88.4%, the EMA 91.3%, and the FDA 95.7%. For NOP, the SMC had an approval rate of 86.2%, the EMA of 93.8%, and the FDA of 88.8%. The consensus decision rate among agencies was 88.4% for OP and 84.4% for NOP. The main clinical driver for divergent decisions for OP was nonrandomized trial design and low patient numbers. Comparing the approved indication wordings, the highest similarity was between the SMC and the EMA, and lowest for the FDA and the EMA. Investigating label strictness, the FDA numerically had the highest but not‐statistically significant number of strict labels. The approval rate stratified by disease area (OP and NOP) differed among the SMC, the EMA, and the FDA. High concordance in regulatory decisions was observed between agencies for OP as well as NOP. Reasons for divergent decisions regarding OP were mainly due to scientific uncertainties. Comparing strictness of indications, numerical but no statistically significant differences were observed between agencies.